Associations between mental health conditions in pregnancy and maternal socioeconomic status: a population-based retrospective cohort study in Ontario, Canada - Qun Miao; Gwyneth Zai; Ian Joiner; Jessica Burnside; Mark Walker (BMC Women's Health)
Abstract Background The World Health Organization has recognized maternal mental illness as an emerging issue. Previous studies have indicated that maternal mental illness is associated with socioeconomic status (SES). However, there is a lack of research concerning the mental health of pregnant people with low SES in Ontario, Canada. In this study, we examined associations between mental health conditions during pregnancy and two SES indicators: the pregnant person’s residential neighbourhood income and education level. Methods A population-based retrospective cohort study was conducted, consisting of all singleton pregnancies resulting in stillbirths or live births in Ontario hospitals from April 1, 2012, to March 31, 2021. Data were linked from the BORN Information System database, Canadian Institute for Health Information Discharge Abstract Database, and Canadian Census. Poisson regression with robust error variance models was performed to estimate the relative risks of anxiety, depression, anxiety and/or depression, or any mental health condition during pregnancy, by SES indicator. We adjusted for maternal age, obesity status in pre-pregnancy, certain pre-existing maternal health conditions, substance use during pregnancy, race, and rural or urban residence. Results Within the cohort (n = 1,202,292), 10.5% (126,076) and 8.1% (97,135) of pregnant individuals experienced anxiety and depression, respectively, and 15.8% (189,616) had at least one mental health condition during pregnancy. The trend test (p < 0.0001) showed a significant downward trend in the total rates of mental health conditions by increasing SES quintiles. Pregnant individuals in the lowest neighbourhood income quintile tended to have a higher risk of anxiety (aRR: 1.24, 95%CI: 1.22–1.27), depression (aRR: 1.56, 95%CI: 1.52–1.59), anxiety and/or depression (aRR: 1.13, 95%CI: 1.11–1.15), or any mental health condition (aRR: 1.18, 95%CI: 1.16–1.19). Similarly, pregnant people living in the lowest education level neighbourhoods had higher likelihoods of anxiety (aRR: 1.66, 95%CI: 1.62–1.69), depression (aRR: 2.09, 95%CI: 2.04–2.14), anxiety and/or depression (aRR: 1.42, 95%CI: 1.39–1.44), and any mental health condition (aRR: 1.41, 95%CI: 1.38–1.43). Conclusions Despite a universal healthcare system, the variations in mental health prevalence and risk during pregnancy based on SES suggest health inequity in Ontario, Canada. Future studies are needed to examine the mechanisms of this health inequity to guide policy makers in reducing disparities in Ontario.